Numerical analysis of a tethered‐buoy mooring system for a prototype floating wind farm - Guodong Liang; Finn‐Christian Wickmann Hanssen; Karl Otto Merz; Zhiyu Jiang (Wind Energy, 2024)
Abstract Conventional mooring systems contribute significantly to the cost of floating wind projects, and innovative solutions with cost‐saving potentials are desired. In the present paper, we investigate the fundamental dynamic behavior of an innovative tethered‐buoy mooring system for a prototype wind farm in which two spar floating offshore wind turbines (FOWTs) are moored to five submerged tethered buoys. Numerical decay tests are used to characterize the fundamental frequencies and oscillatory modes of the system. The influence of net buoyancy is established through a parametric study. Finally, the dynamic response of the tethered‐buoy mooring system is compared against two alternative shared mooring configurations with catenary mooring lines. Time‐domain simulations are carried out for one accidental scenario with a parked and an operational FOWT, and one extreme scenario with two parked FOWTs. The results show that net buoyancy has a significant influence on platform motions and mooring loads. Compared to alternative configurations with catenary mooring lines, the tethered‐buoy mooring system exhibits substantially lower mooring tension loads and practically eliminates the threat of snap events. The reduction in the maximum characteristic fairlead tension is up to 85%. The mean positional offset of the wind turbines in the loading direction is larger, up to 36% of the water depth, however, the relative motions are comparable. The mean distance between the FOWTs is even smaller for the tethered‐buoy system. With the application of dynamic inter‐array cables, the proposed tethered‐buoy system can be a promising mooring solution for floating offshore wind farms.